Acute liver injury following methylprednisolone pulse therapy: 13 cases from a prospectively collected cohort. Issue 4 (15th December 2021) - Allgeier, Julian; Weber, Sabine; Todorova, Rumyana; Neumann, Jens; Gerbes, Alexander
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and aim: Drug-induced liver injury (DILI) remains a challenging diagnosis requiring exclusion of other causes of liver injury, concise medical history taking to identify potential causative medication and creation of a plausible temporal relation to attribute said liver injury to a potentially hepatotoxic agent. In spite of corticosteroids being considered an effective treatment for DILI in some patients, methylprednisolone (MPS) has been associated with liver injury of varying severity. Methods: We analyzed data of our prospective study on potentially hepatotoxic drugs (NCT 02353455), identified 13 cases of MPS-associated liver injury and performed an analysis of clinical, laboratory and histopathological characteristics. For all available liver biopsy specimens, expert histopathological analysis was performed. Results: Thirteen patients with a variety of primarily neurologic autoimmune diseases treated with MPS developed subsequent liver injury with a median latency of 5 weeks. Liver injury was severe or required transplantation in six patients. Injury typically occurred after repeated pulsing was hepatocellular and responded swiftly to prednisolone administration. For those patients who received in house-follow up, relapse after discontinuation of immunosuppression was not observed. Histopathological features of MPS-DILI comprised both interface and periportal hepatitis with mixed inflammatory infiltrates, similar to autoimmune hepatitis (AIH) features. Discussion: MPS-related liver injury can be life-threatening, occurs with considerable latency and after repeat dosing. Regular surveillance of hepatic biochemistry should therefore be routinely performed also after discharge to avoid further MPS-related liver injury during repeat application. Swift response to prednisolone but not histologic features can be helpful to discriminate MPS-DILI from AIH.